Workplace Diversity Management: A Corporate Performance Driver - Tinuke M., Fapohunda (International Journal For Research In Business, Management And Accounting, 2016)
Diversity is now a significant human resources management topic due to numerous dynamics producing aspirations of added diversity in people management. Organization management must value the advantages of diversity and this demands noticeable endeavour and understanding merited by both the employees and the organization. It could emphasise several actions that truly value and breathe diversity throughout. This paper puts forth some possibilities including: valuing diversity, achieving people commitment, encouraging inclusion, assistance in family spirit, augmenting people empowerment, unique recruitment and selection schemes, excellent orientation programmes, trainers and mentors with elevated compassionate and social abilities, internal training of human capital, clear performance management plans, career development, instant correction of non performance based workforce assessments, organization strategies that incorporate diversity and diverse top management. Except organization management is concerned with employees’ best interests, effective diversity management becomes impossible therefore, they must somewhat wheel their focus increasingly to provide for organization members.